2011
DOI: 10.2320/matertrans.m2010401
|View full text |Cite
|
Sign up to set email alerts
|

Foaming Agents for Powder Metallurgy Production of Aluminum Foam

Abstract: Metallic foams are commonly produced using hydride foaming agents. Carbonates are safer to handle than hydrides; however, their use in the powder metallurgy (PM) route to obtaining a fine and homogenous cell structure has not been evaluated. In this study, carbonates and hydroxides were investigated as foaming agents for the production of Al-Si-Cu alloy foams by the PM route. The thermal decomposition behavior of the foaming agents was evaluated in conjunction with the cell structure of the aluminum foams prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 4 publications
0
43
0
1
Order By: Relevance
“…However it is found that melt foaming process is best for fabrication of Mg-foam because it can be easily controlled and is cheaper than others [1]. Different foaming agents were found for production of Al foam [15]. However, in conclusion it is found that CaCO 3 and Dolomite are the best suitable agents due to their cost and stability [15].…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…However it is found that melt foaming process is best for fabrication of Mg-foam because it can be easily controlled and is cheaper than others [1]. Different foaming agents were found for production of Al foam [15]. However, in conclusion it is found that CaCO 3 and Dolomite are the best suitable agents due to their cost and stability [15].…”
mentioning
confidence: 89%
“…Out of which there are two methods of fabricating the cellular Mg-foams i.e. melt foaming method also known as Alporas Method and powder metallurgy method (Fraunhofer method) [15]. However it is found that melt foaming process is best for fabrication of Mg-foam because it can be easily controlled and is cheaper than others [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mass reduction rates of dolomite, magnesium carbonate, and calcium carbonate obtained by thermogravimetric analysis-differential thermal analysis (TG-DTA) are shown in Figure 5 [9]. Dolomite started to decompose at 773 K and rapidly decomposed above 1013 K. In contrast, magnesium carbonate decomposed from 793 to 993 K and calcium carbonate from 993 to 1113 K. Calcium carbonate is ineffective for multiple additions, because it does not decompose at 968 K, at which foam produced using dolomite shrinks.…”
Section: Methods Of Preventing Shrinkagementioning
confidence: 99%
“…The foams produced using dolomite and magnesium carbonate have a fine and homogenous cell structure [9][10][11]. The foam produced using TiH 2 shows the coalescence of cells, before rupture by gravity [12,13].…”
Section: Introductionmentioning
confidence: 99%